2004
DOI: 10.1002/cncr.20559
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the nipple and breast ducts revisited

Abstract: BACKGROUND Increasing interest in the intraductal approach to the breast has necessitated revisiting the anatomy of the breast. METHODS Using six different complementary in vivo and in vitro approaches, the authors determined the number, distribution, and anatomic properties of the ductal systems of the breast, which extend from the nipple orifices to the terminal duct lobular units. RESULTS More than 90% of all nipples examined contained 5–9 ductal orifices, generally arranged as a central group and a periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
15

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 11 publications
2
104
0
15
Order By: Relevance
“…In 2004, Love and Barsky used several in vivo and in vitro approaches to determine the number, distribution, and anatomic properties of the ductal system of the human breast (i.e., from the nipple orifices to the terminal duct lobular units; ref. 20). They showed that >90% of all nipples examined contained five to nine ductal orifices.…”
Section: Discussionmentioning
confidence: 98%
“…In 2004, Love and Barsky used several in vivo and in vitro approaches to determine the number, distribution, and anatomic properties of the ductal system of the human breast (i.e., from the nipple orifices to the terminal duct lobular units; ref. 20). They showed that >90% of all nipples examined contained five to nine ductal orifices.…”
Section: Discussionmentioning
confidence: 98%
“…Despite this discrepancy, Love and colleagues have shown that cannulation of all the orifices on the nipple surface is sufficient to fill all the ductal systems and that fluid instilled into the ducts reaches the terminal duct lobular units (TDLU; ref. 19). In 2004, Goulet and colleagues confirmed this in a pilot study in which 3 to 5 mL of nanoparticles containing 6% epirubicin was administered into tissue specimens postmastectomy and assessed pathologically, showing that intact epirubicin was seen in the terminal lobules in 62% of specimens (26).…”
Section: Introductionmentioning
confidence: 95%
“…The description of the number of ducts found per breast depends on the technique of study (18). Researchers who have cannulated the ductal orifices in the nipple in vivo, all confirm 5 to 9 ductal systems (19)(20)(21)(22), whereas those who have transected the nipple in mastectomy specimens have documented 22 to 25 tubular structures (21,(23)(24)(25). Despite this discrepancy, Love and colleagues have shown that cannulation of all the orifices on the nipple surface is sufficient to fill all the ductal systems and that fluid instilled into the ducts reaches the terminal duct lobular units (TDLU; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Women occasionally detect a normal lactiferous sinus as a palpable finding at self-examination. In the typical breast, there are 9-20 orifices that drain the segments at the nipple (Kopans 2007, Love 2004). …”
Section: Anatomy Of the Nipple And Areola: Nipple-areolar Complexmentioning
confidence: 99%